ASUHAN KEPERAWATAN NYERI AKUT PADA NY.T DENGAN HIPERTENSI DI PANTI PELAYANAN SOSIAL LANJUT USIA DEWANATA CILACAP - Asri Meliyana; Wasis Eko Kurniawan (Bajang Institute, 2023)
Hypertension is a condition where blood pressure rises, namely systolic blood pressure ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg. Treating hypertension non-pharmacologically can be done by doing foot soak therapy with warm water. Research to aim to provide nursing care for acute pain in Mrs. T with foot soak using warm water against hypertension patients at the Dewanata Cilacap Elderly Social Service Home which was conducted on May 08-10, 2023. Respondents in this study were one person with a selection of six elderly people in guesthouse 6. The data collected contains assessment data, diagnoses, interventions, implementation and evaluation. The intervention carried out is foot soak therapy using warm water carried out for 7x24 hours. There was a decrease in the initial pain scale of 7 to scale 3 and a decrease in blood pressure on the first day to the third day. The findings indicate that warm water foot bath therapy can reduce blood pressure. A three-day evaluation which found that physiological injury agents associated with acute pain showed that the problem had been resolved